A case of low-grade fibromyxoid sarcoma with unusual central necrosis in a 77-year-old man confirmed by FUS-CREB3L2 gene fusion - Kurisaki-Arakawa, Aiko (Int J Surg Case Rep, 2014)
INTRODUCTION: Low-grade fibromyxoid sarcoma (LGFMS) is a rare soft tissue tumor typically affecting young to middle-aged adults. Despite its otherwise benign histologic appearance and indolent nature, it can display fully malignant behavior, and recurrence and metastasis can occur even decades after diagnosis. PRESENTATION OF CASE: Herein, we report a case of LGFMS in the buttock of a 77-year-old man. Magnetic resonance imaging uncovered a well-demarcated tumor measuring 27 × 20 mm with a slightly high intensity on T1-weighted images (WIs) and heterogeneously high intensity on T2-WIs. Histologically, the tumor was composed of bland spindle-shaped cells in a whorled growth pattern with alternating fibrous and myxoid stroma. The tumor stroma was variably hyalinized with arcades of curvilinear capillaries and arterioles with associated perivascular fibrosis. Unusual histology, such as central necrosis and cystic formation, was also noted. Reverse transcription polymerase chain reaction from a formalin-fixed, paraffin-embedded biopsy specimen revealed a FUS-CREB3L2 gene fusion (exon6/int/exon5), leading to the diagnosis of LGFMS. DISCUSSION: To the best of our knowledge, this is the second oldest patient to be diagnosed with LGFMS. CONCLUSION: At the time of this report, the patient was alive with no evidence of the disease 4 months after diagnosis without any adjuvant therapy.